Au/CdS Core-Shell Sensitized Actinomorphic Flower-Like ZnO Nanorods for Enhanced Photocatalytic Water Splitting Performance - Ying Li; Tie Liu; Shuang Feng; Wenshu Yang; Ying Zhu; Yingying Zhao; Zhiyan Liu; Haibin Yang; Wuyou Fu (Nanomaterials, 2021)
Herein, a novel actinomorphic flower-like ZnO/Au/CdS nanorods ternary composite photocatalyst is prepared to extend the light-responsive range, reduce the photogenerated charge carriers recombination, and ultimately improve the water splitting performance. Flower-like ZnO nanorods are synthesized by a chemical bath method and the CdS nanoparticles are sensitized by successive ionic layer adsorption and reaction method. Then the Au nanoparticles as co-catalysts are introduced by the photodeposition method to modify the interface of ZnO/CdS for reducing the photogenerated electron recombination rate and further improving the performance of water splitting. Detailed characterizations and measurements are employed to analyse the crystallinity, morphology, composition, and optical properties of the flower-like ZnO/Au/CdS nanorods samples. As a result, the flower-like ZnO/Au/CdS nanorod samples present significantly enhanced water splitting performance with a high gas evolution rate of 502.2 μmol/g/h, which is about 22.5 and 1.5 times higher than that of the pure ZnO sample and ZnO/CdS sample. The results demonstrate that the flower-like ZnO/Au/CdS nanorods ternary composite materials have great application potential in photocatalytic water splitting for the hydrogen evolution field.